2014
DOI: 10.3109/10717544.2013.879398
|View full text |Cite
|
Sign up to set email alerts
|

N-trimethyl chitosan (TMC)-modified microemulsions for improved oral bioavailability of puerarin: preparation and evaluation

Abstract: The aim of this research was to increase the oral bioavailability of puerarin by N-trimethyl chitosan-modified microemulsions (TMC-MEs) loaded with puerarin. Different concentrations of TMC-modified microemulsions were prepared in our study, and then evaluated for particle size, zeta potential, morphological observation and changes of the microenvironment polarity of inner oil core. It was shown that the zeta potential of the microemulsion was increased with the increasing concentration of TMC, and the peak va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Puerarin has poor water solubility and intestinal permeability, which limits its clinical application. To prepare effective, strong, and long‐term preparations of puerarin with a high oral bioavailability, the structural and dosage form of puerarin can be improved via structural modification, microemulsion, nanoparticles, and other methods (Liao et al, 2015; Luo et al, 2011; Wu et al, 2018; Zhao et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Puerarin has poor water solubility and intestinal permeability, which limits its clinical application. To prepare effective, strong, and long‐term preparations of puerarin with a high oral bioavailability, the structural and dosage form of puerarin can be improved via structural modification, microemulsion, nanoparticles, and other methods (Liao et al, 2015; Luo et al, 2011; Wu et al, 2018; Zhao et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with free puerarin, 93 the bioavailability of puerarin MEs was significantly enhanced in treating neurodegenerative diseases and tumors. 94–98 They could also act as a transdermal drug delivery system to improve skin penetration. The total flavonoids of araceae were encapsulated into MEs and it was found that the transdermal flux of its two main active ingredients, schaftoside and isoschaftoside, was 3.72 times and 5.92 times higher than that of the aqueous suspension, respectively.…”
Section: Nano-drug Delivery Systems For Tcmmentioning
confidence: 99%
“…Powerful absorption enhancing agents such as ethyl oleate (Yu et al., 2011; Tang et al., 2013) and N-trimethyl chitosan chloride (Liao et al., 2015) were added into the formulation, not only as the oil phase, but also improved the oral bioavailability of puerarin. When N-trimethyl chitosan chloride was added to the microemulsion formulation, the relative bioavailability was enhanced more than five times compared with control microemulsion (Liao et al., 2015). Through combining phospholipid complex technology and microemulsion, the relative oral bioavailability of puerarin phospholipid complex was 3.16-fold higher than puerarin(Wu et al., 2018).…”
Section: Drug Delivery Systems Of Puerarinmentioning
confidence: 99%
“…Upon oral administration, puerarin-loaded microemulsions significantly improved the bioavailability of puerarin from 1.2-fold to 15.2-fold compared with corresponding puerarin control groups (Wu et al, 2009;Yu et al, 2011;Tang et al, 2013;Liao et al, 2015;. Powerful absorption enhancing agents such as ethyl oleate (Yu et al, 2011;Tang et al, 2013) and N-trimethyl chitosan chloride (Liao et al, 2015) were added into the formulation, not only as the oil phase, but also improved the oral bioavailability of puerarin. When N-trimethyl chitosan chloride was added to the microemulsion formulation, the relative bioavailability was enhanced more than five times compared with control microemulsion (Liao et al, 2015).…”
Section: Microemulsions and Self-microemulsifying Drug Delivery Systemsmentioning
confidence: 99%